Allergic rhinitis, bronchial asthma and other allergies in patients with Alzheimer’s disease: unnoticed issue - Bożek, Andrzej; Bednarski, Piotr; Jarzab, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Allergic diseases are becoming more prevalent in elderly patients. Allergic diseases have been observed in patients with Alzheimer’s disease (AD). The prevalence of atopic bronchial asthma, allergic rhinitis and atopic dermatitis was analyzed in such elderly Polish population. Aim : Analysis of the presence of allergic diseases in the patients with AD in Poland, including asthma, allergic rhinoconjunctivitis and atopic dermatitis. Material and methods: The recruitment of subjects with AD was conducted at 6 sites representative of Polish rural and urban areas, and 1060 subjects with a mean age of 69.2 ±5.1 years were screened. Medical examinations, an original questionnaire, skin prick testing for common aeroallergens and appropriate serum-specific IgE assays were performed. Results : Probable atopy was diagnosed in 234 (22.1%) analyzed patients, including 127 women (21.5% of women) and 234 men (22.8% of men). The average prevalence associated with age and sex in this population for bronchial asthma was 2.9%, atopic dermatitis/eczema was 0.6%, seasonal allergic rhinitis was 6.6%, perennial allergic rhinitis was 11.1% and polymorphous atopic disease was 4.4%. The most frequent positive results were recorded for the following allergens: mixed grass, Dermatophagoides pteronyssinus, Dermatophagoides farina and Alternaria . Conclusions : One-fifth of diagnosed patients with AD have allergic disease requiring treatment.